The Strengthening of Theological Base: a Pattern of Islam Wasathiyah Indonesia According to The Maqashid Shariah - Nur Fauzi; Abd Wahid (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
This study aims to find the concept of Indonesian Islamic moderation from the perspective of maqashid shariah and tries to present forms of Islamic moderation that follow the Qur'an and al-hadith (maqashid shariah). By conducting qualitative research with a descriptive approach through library research methods that focus on observing (examining) previous research studies and analyzing the mils and Huberman models related to conformity with maqashid sharia. This study resulted in the primary forms of Indonesian Islamic moderation, namely: the state of Indonesia, neither a radical religion nor a liberal religion. It is conceptualized in five aspects belonging to the wasathiyah concept, namely: Maintaining Religion (Hifdzu al-din), Nurturing the Soul (hifdzu al-nafs), Maintaining Intellect (hifdz al-aqli), Caring for offspring (hifdz al-nasl). ), Maintaining property (hifdz al-mal). So, the presence of maqashid sharia as a spirit with these five principles in maintaining the integrity of Religion and the State ensures that love for Religion and the State can save humanity and maintain the dignity of Islam itself.